A retrospective look at the US productivity growth resurgence - Dale W. Jorgenson; Mun S. Ho; Kevin J. Stiroh (Federal Reserve Bank of New York, 2007)
It is now widely recognized that information technology (IT) was critical to the dramatic acceleration of U.S. labor productivity growth in the mid-1990s. This paper traces the evolution of productivity estimates to document how and when this perception emerged. Early studies concluded that IT was relatively unimportant. It was only after the massive IT investment boom of the late 1990s that this investment and underlying productivity increases in the IT-producing sectors were identified as important sources of growth. Although IT has diminished in significance since the dot-com crash of 2000, we project that private sector productivity growth will average around 2.5 percent per year for the next decade, a pace that is only moderately below the average for the 1995-2005 period.
Keywords: O3; O4; 330; productivity growth; information technology